Deteksi Dini Gangguan Kognitif dan Depresi Pada Lansia - Resti Rahmadika Akbar; Dian Ayu Hamama Pitra; Mutiara Anissa; Yuri Haiga; Rahma Triyana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Increasing the number of elderly people needs to be followed by programs that can maintain the quality of life of the elderly. The ratio of elderly dependence on the productive population is increasing. For that, we need a program so that physical and social changes in the elderly do not reduce the independence of the elderly. Physical changes in the form of cognitive disorders namely decreased brain function so that activities related to the ability of attention, concentration, calculation, decision making, reasoning, and abstract thinking. Social changes in the form of job loss, loneliness, risk of disease, can be a trigger for depressive disorders in the elderly. The purpose of this activity is for all parties to have a role in the early detection of cognitive disorders and depression as well as the elderly who have symptoms can be treated early